Analisis Faktor yang Berpengaruh terhadap Ketimpangan Pendapatan di Indonesia - Yudhistira Ardana (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
This study aims to analyze what factors affect the income inequality inIndonesia. The method used in this research is to perform regressionanalysis of panel data using E-views 10. The variables used in thisstudy are Gini Ratio as Y variable, while Local Revenue, GeneralAllocation Fund, Capital Expenditure, Agricultural SectorContribution, Contribution of Manufacturing Sector, Service SectorContribution, Financial Sector Contribution, Domestic Investment andForeign Investment as variable X. The province used in this research is32 provinces. The result of the research, the variables that influence thedecreasing inequality of income distribution are DAU, capitalexpenditure, contribution of agriculture sector, contribution ofmanufacturing sector and financial sector contribution. While PAD,service sector, PMDN and PMA, positively influence to increaseinequality income distribution